COVID-19 And Higher Education: Effects On The Training Of Panamanian Teachers (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The last few months have been totally disruptive for teaching in Panama - and around theworld. The response of the Panamanian public system - and of the states - has beendysfunctional and surprising at first and calmer as the months have passed, but this has ledto learning what teachers should be like in the future for the new educational system that iscoming, according to understanding of the lessons learned this will be the State's response ,so 'before we give a definite opinion about education that we think is preferable, we shouldhave some idea of the kind of person we want to produce'. In essence we ask ourselveswhether teachers should continue to promote dual intellectual and character education inour students and use new technologies as one more tool, that is, a very useful tool (virtualplatforms, videoconferencing programs, etc.) or on the contrary new technologies arealready an essential part of teaching and are not a more useful tool, so all our students andall our teachers must be technological.